PENGEMBANGAN DESAIN INTERIOR KELAS DAN FURNITUR SARANA BELAJAR TK KARYA PUTRA SESUAI ERGONOMI ANAK USIA DINI - Andrianawati, Aida; Haristianti, Vika (Nindikayla Institute, 2023)
Children are the main potential for the future of a nation. They are not only the forerunners of the nation's successors but also as individuals who are expected to have high competitiveness. Personality and individual qualities in adulthood are greatly influenced by the experiences and education obtained in childhood. PAUD schools for children aged 0-4 years apply the concept of playing while learning (recreational learning) which aims to help children's self-development. Karya Putra Kindergarten was chosen as the target partner for the Community Service program related to fostering the development of quality education which must start from an early age, namely at the PAUD / Kindergarten level. Karya Putra Kindergarten really needs help to organize the interior of the classroom with limited space and increasing student capacity. Likewise, adapting learning methods in early childhood schools requires a comfortable learning space concept, so it is necessary to have furniture and layout that is in accordance with early childhood ergonomics standards. By completing the right design, it is hoped that it will be the right solution to the problems that occur in the study room.